Characterization of the complete plastome of Atropanthe sinensis (Solanaceae) - Zhilin Jiang; Ziyoviddin Yusupov; Xianhan Huang; Dilmurod Makhmudjanov; Komiljon Tojibaev; Tao Deng (Mitochondrial DNA. Part B. Resources, 2019)
Atropanthe sinensis Pascher (genus Atropanthe, family Solanaceae) is an endangered and medical important plant of China. Here, we report the complete plastome of A. sinensis, which was found to be 156,565 bp in length and encodes 114 annotated known unique genes, including 80 protein-coding genes, 4 ribosomal RNAs, and 30 transfer RNAs. Among them, 10 coding genes contained one intron each and two genes (clpP and ycf3) contained two introns each. The result of the phylogenetic analysis showed that genera Scopolia and Przewalskia were placed as sister groups to the Atropanthe.